Kualitas Pelayanan di Bidang Administrasi dalam Rangka Pelayanan Publik di Kantor Distrik Warmare Kabupaten Manokwari - Septer Wonggor; Sutrisno Sutrisno; Indiati Indiati (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This research aims to determine the quality of service in the administrative sector in the context of public services at the Warmare District office, Manokwari Regency. The research method used is a qualitative research approach. In the data collection technique, the author uses an interview technique and then obtains data from the results of the interview. From the research results, it can be concluded that the people of Warmare District are satisfied with the services provided by the Warmare District Public Services Department in terms of reliability regarding reliability in handling every public complaint, reliability in terms of time and accuracy of the service process. Judging from the assurance aspect, especially security at the Warmare Subdistrict Office, Manokwari regency, it has shown efforts to improve the quality of its services related to providing a sense of security for the community, namely by placing parking attendants who help secure conditions in the parking lot. Then any items left in the service room will be kept by the staff until the owner picks them up